FACTORS AFFECTING THE SUSTAINABILITY OF SHARIA MUTUAL FUND RETURNS IN THE 2019-2021 PERIOD - Marsono, A Dewantoro; Fadliana, Zahra Zhafira (Proceeding International Seminar of Islamic Studies, 2023)
Investment is an important thing to do for a better life to achieve life’s sustainability. One of them is through sharia mutual funds. This study aims to determine and analyse the effect of inflation, mutual fund age, and mutual fund size on sharia mutual fund returns. The population of the study is the sharia mutual fund that was listed in BEI in the period of 2019-2021. The data was then analysed using the panel data regression analysis method. The result shows that inflation and mutual fund age have a significant negative effect on the sustainability of sharia mutual fund returns. However, mutual fund size significantly positively affects the sustainability of sharia mutual fund returns. The F-test shows that inflation, mutual fund age, and mutual fund size simultaneously influence the sustainability of sharia mutual fund returns.